Microplankton dynamics in a perennially ice-covered Antarctic Lake - Lake Hoare - Roberts, EC; Priscu, JC; Laybourn-Parry, J (2004)
1. Temporal and spatial variation in planktonic abundance, biomass and composition were determined in Lake Hoare (McMurdo Dry Valleys, Antarctica) over two summer seasons (1996–97 and 1997–98). 2. Phototrophic nanoflagellates (PNAN) dominated planktonic biomass, with a mean monthly biomass ranging between 27.3 and 40.4 lg C L)1. The deep chlorophyll maximum was mainly composed of cryptophytes (>87% of total PNAN biomass) and varied in depth between 6 and 12 m. 3. Maximum bacterial concentration was 11.8 · 105 cells mL)1. Bacterial abundance showed relatively little temporal variation, with the exception of a drop in numbers that occurred in late November of both years studied. 4. Ciliates were the most successful heterotrophic protozoan group, with a mean monthly biomass (1.2–3.2 lg C L)1) being typically at least double that of heterotrophic nanoflagellate (HNAN) biomass (0.1–0.7 lg C L)1). 5. Microbial processes within this lake appear to be dominated by bottom up control. The relative importance of allochthonous inputs into the lake (from the ice-cover and stream flow) and autochthonous recycling (by microzooplankton regeneration) are considered. 6. Results from a horizontal transect indicate that the permanence of the main sample hole may have enhanced planktonic biomass over a relatively small spatial scale.